معالجة نقص إنتاجية التقطير الشمسي التقليدي باستعمال المبادل الحراري في المناطق الجافة - عاشور, أحمد; فريد, عبد الباسط; لبزة, خير الدين (universty of elouedجامعة الوادي, 2021)
يهدف هذا العمل إلى تحسين أداء المقطرات الشمسية باستخدام الهواء الساخن المسخن في مجمعات الطاقة الشمسية المسطحة (العمل في حالة الحمل القسري). في الدراسة التجريبية الحالية ، تم تركيب مبادل حراري (أنبوب نحاسي قطره 1.4 سم) في قاع حوض التقطير. يتم ضخ الهواء بالقوة بواسطة مروحة تعمل بألواح شمسية في مجمع الطاقة الشمسية المسطح. يقوم الأخير بتسخين الهواء ثم إدخاله في المبادل الحراري. يؤدي دفع الهواء الساخن إلى المبادل الحراري، الذي يتم تسخينه بواسطة المجمع الشمسي ، إلى تبادل كمية الحرارة بين أنابيب المبادل الحراري التي يمر من خلالها الهواء الساخن ومياه الحوض المالحة ، ويؤدي هذا التعديل إلى زيادة معدل التسخين من مياه الحوض، مما يزيد من كمية التبخر وبالتالي تحسين إنتاجية الماء المقطر. تم فحص التقطير الشمسي المعدل بشكل تجريبي على عمق ماء مميز يبلغ 3 سم (7.5 لتر من الماء المالح) ، وتمت مقارنة الأداء في نفس الوقت مع جهاز التقطير التقليدي على عمق ماء مميز يبلغ 1.5 سم (2.5 لتر من الماء المالح). أوضحت النتائج التجريبية أن الحد الأقصى للحاصل اليومي 2.5 لتر/م2/اليوم لنواتج التقطير التقليدية على عمق 1 سم ، والحد الأقصى للإنتاج اليومي 7.5 لتر/ م2/اليوم لنواتج التقطير المعدلة على عمق 3 سم. أدت هذه القيم إلى تحسين الإنتاجية اليومية بنسبة 25٪ مقارنة بنتائج المقطرات التقليدية.This work aims to enhance the performance of solar distillates by using the heated hot air in the flat solar collectors (working in a forced pregnancy). In the present experimental study, a heat exchanger (copper tube a diameter 1.4 cm) is installed at the bottom of the distillation trough. The air is pumped by a fan powered by solar panels into the flat solar collector forcibly. The latter heats the air and then feeds it into the heat exchanger. The push of hot air into the heat exchanger, heated by the solar collector leads to an exchange in the amount of heat between the heat exchanger tubes through which the hot air passes and the saline basin water, this modification leads to an increase in heating rate of the basin water, increasing the amount of evaporation and thus enhancing water productivity distilled. The modified solar distillation was experimentally examined at characteristic water depth of 3 cm (7.5 L of salt water), and the performance was compared at the same time with the conventional distillation device at characteristic water depth of 1.5 cm (2.5 L of salt water). The experimental results showed that the maximum daily yield of 2.5 L/m2 per day for the conventional distillate at a depth of 1 cm, the maximum daily yield of 7.5 L/m2 per day for the modified distillate at a depth of 3 cm. These values improved daily productivity by 25%, compared to the results of conventional distillers.
مذكرة ماستر فيزياء
Keywords: التقطير الشمسي؛ جامع الطاقة الشمسية؛ أنابيب النحاس؛ مبادل حراري؛ هواء ساخن؛ الماء المقطر؛ الطاقة الشمسية.; Solar still; Solar collector; Copper tubes; Heat exchanger; Hot air; Distilled water; Solar energy